TYPES OF PROCESS IN THE CLAUSES OF EMINEM'S 'HOUDINI' SONG LYRICS: A TRANSITIVITY ANALYSIS - Adhitya Darmawan; Nada Humaida Rohmah (Leksema: Jurnal Bahasa dan Sastra, 2025)
This article discusses a transitivity analysis under the scope of systemic functional linguistics and it focuses on the types of processes in the clauses of Eminem’s Houdini song lyrics. Apart from just the processes, this paper also aimed to know how each stage of the song lyrics has different numbers of processes, so that the social construction from the staging can be seen further. This research is qualitative-descriptive since the data are multiple and holistically constructed. The data were collected from the transcription of the song lyrics which were then analyzed by using Spradley’s (1980) model of analysis. The stages of the analysis comprise domain, taxonomy, componential, and cultural theme analysis. The results show that the song mostly uses relational identifying process with as many as 46 data. Next, the stage that has the most processes is the third verse with total 46 data. Additionally, the verses carry the main narrative and thematic contents so that they have more processes, often repetitive, than the other song sections. The conclusion is that relational identifying processes are mostly used to identify or show the presence of Eminem, Slim Shady, and the controversy Eminem brings in the new album as well as what he already brought in the old albums.